Nuclear energy debate - Healey, Justin (Issues in society (Balmain, N.S.W.) ;, 2012)
The debate over the introduction of nuclear power in Australia has recently become more heated in light of safety concerns over the nuclear reactor meltdown emergency in Japan. Australia has also just committed to a carbon trading scheme to address its reliance on coal-fired energy and reduce greenhouse emissions. With 40% of the world's uranium located in Australia, the economic, environmental and health considerations are significant. This book contains an overview of global nuclear energy use and production, and presents a range of current opinions debating the pros and cons of Australia's.